A Supramolecule‐Triggered Mechanochromic Switch of Cyclodextrin‐Jacketed Rhodamine and Spiropyran Derivatives. (7th December 2015) - Wan, Shulin; Ma, Zhiyong; Chen, Chen; Li, Fangfei; Wang, Feng; Jia, Xinru; Yang, Wantai; Yin, Meizhen
Abstract : An innovative approach for covalent‐bond‐activated mechanoresponse by complexing rhodamine or spiropyran with cyclodextrin (CD) is reported. This approach endows diverse fluorophores with perfect mechanochromism by introducing a supramolecular system. Unique characteristics such as noncovalent chemical modification and convenient preparation make this approach promising for practical applications. The strong hydrogen bonds provided by CD play a crucial role in triggering the mechanochromic switch. First, the hydrogen bonds seize both sides of the fluorophore's weak chemical bonds and tightly lock the fluorophore in the cavity of CD. Second, the hydrogen bonds prompt the aggregation of complex inclusions in large ordered arrays and strengthen the molecular interactions. In this way, the weak chemical bonds can focus more external force and stretch more easily upon shearing (quantified). This is the first report of supramolecule‐triggered mechanochromic switches. This study opens an avenue to correlate a mechanochemical reaction with a supramolecular system. Abstract : An innovative approach for covalent‐bond‐activated mechanoresponse by complexing rhodamine or spiropyran with cyclodextrin is reported. This is the first report of supramolecule‐triggered mechanochromic switches. This approach endows diverse fluorophores with perfect mechanochromism by introducing a supramolecular system. This study opens an avenue to correlate mechanochemical reaction with a supramolecular system.